(3GfYcGSGJ GdJfejI GdeSJOGeI Ydi eYGjjQ JUeje CHfjI GdJYdje GdCSGSj (B: s (3GdCeQjcjI ddeOGQS YGdjI GdCOGA (BCHPS (3QDjI ddeYGjjQ GdeUQjI aj VhA eYGjjQ (B/ s - (3OYGA YHOGdLdjd MSjf YHOGdeLjOs; (3LeGd CMeO YHOGdMejO (B: s; (3gTGe SGeM MSjf SGeM (B: s ((3GdbGgQI (B: s (3OYGA YHOGdLdjd MSjf YHOGdeLjO (B: s, 2013)
(3aj YGe (B1990 (3Je hVY Chd eYGjjQ JUejejI ddCHfjI GdeOQSjI ai eUQ h cGfJ deOGQS GdJYdje GdCSGSi dEbdje GdbGgQI GdcHQi h CUHMJ OQGSI eQLYjI gGeI ai gPG GdeLGd (B. (3h HYO CcKQ ef YTQjf YGeB h eY JQGLY GdGgJeGe HgPg GdeYGjjQ h YOe JMOjKgG h eY GdJMhd fMh eaGgje GdYeQGf GdeSJOGe h HQhR eaGgje GdCHfjI GdeOQSjI GdeSJOGeI JHOh GdMGLI edMI dWQM gPG GdJMhd Ydi GdeYGjjQ GdeUQjI dJUeje GdCHfjI GdeOQSjI dJchf YedjI GdJMOjK YedjI JWhjQ MbjbjI dEMOGK JZjQ Ydi CQV GdhGbY s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJfejI GdeSJOGeIs; (3GdNOeGJ GdJYdjejIs; (3GdeOGQS YGdjI GdCOGAs